2018
DOI: 10.4067/s0718-95162018005000701
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield of Phaseolus vulgaris in a function of application of boron in soil

Abstract: The objective of this study is to evaluate the effects of sources and doses of boron on the physiological quality and production yield of Phaseolus vulgaris grown using a central pivot irrigated system on a tropical climate region. The experiment was a 4x5 factorial design representing four sources of boron (boric acid, borax, borogran and FTE BR 12) and five boron doses (0, 1, 2, 3 and 4 kg ha -1 ), with four replications. The following parameters were measured: relative chlorophyll index, transpiration, CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 8 publications
2
14
0
4
Order By: Relevance
“…In this way, the chlorophyll readings are a nondestructive and fast method to N determination in plants (Maia et al, 2013). In recent studies developed by Flores et al (2018) no increase was observed in the RCI content as a function of soil B application, like those observed in this work.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this way, the chlorophyll readings are a nondestructive and fast method to N determination in plants (Maia et al, 2013). In recent studies developed by Flores et al (2018) no increase was observed in the RCI content as a function of soil B application, like those observed in this work.…”
Section: Discussionsupporting
confidence: 76%
“…. In recent studies, Flores et al (2018) evaluated the effect of four boron sources. They applied five B rates on the soil in an irrigated system of common bean.…”
Section: Introductionmentioning
confidence: 99%
“…The variations in the effects for the chlorophyll content in the plants of soil fertilization treatments with varied doses of micronutrient (adopting B as reference) revealed that the supply of up to 4.0 kg ha -1 of the micronutrient did not affect the chlorophyll index at 28 and 46 days after emergence (Flores et al 2018a), the fertilization with 4.39 kg ha -1 promoted a higher chlorophyll index at 40 days after germination (Flores et al 2017), while doses up 6.0 kg ha -1 reduced pigment rates in common bean leaves (Flores et al 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Investigating such physiological parameters, Warren (2004) observed that the positive response of photosynthesis to nutrient supply was not accompanied by changes in gs and Ci. In the work of Flores et al (2018a), increasing doses of micronutrients (sources with wide-ranging solubilities) applied to the soil also did not affect Ci and gs; however, in different soils, the application of Zn, Cu and B at different levels improved A, gs, total chlorophyll and fruit production (Ilyas et al 2015). It should be noted that in the present study grain yield per plant (MGP) was not affected by treatments (Table 7), a fact similar to that observed by Mallarino et al (2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation